2019
DOI: 10.5897/joda2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

Participatory evaluation of maize varieties for the management of maize gray leaf spot disease (Cercospora zeae maydis) at Gondar Zuria district, northwest Ethiopia

Abstract: Gray leaf spot is one of the major constraints of maize production in Ethiopia where warm humid environmental condition is prevailing. A field experiment was conducted in Gondar zuria district of western Ethiopia during 2016/17 and 2017/18 cropping season with the aim to evaluate effective maize varieties for the management of maize gray leaf spot disease. The experiment was laid out in Randomized Complete Block Design (RCBD) in three replications. Nine improved varieties, that is, SBRH, Gibie 2, Gibie 3, Arge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…GLS poses a serious problem to maize production with estimated yield losses of more than 70% (Liu et al, 2016) under favorable conditions. The disease caused severe economic losses in SSA (Ward, 1996;Vivek et al, 2010;Kibata et al, 2011;Bekeko et al, 2018;Yigrem and Yohannes, 2019). Therefore, maize breeding programs in SSA typically incorporate GLS resistance in product pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…GLS poses a serious problem to maize production with estimated yield losses of more than 70% (Liu et al, 2016) under favorable conditions. The disease caused severe economic losses in SSA (Ward, 1996;Vivek et al, 2010;Kibata et al, 2011;Bekeko et al, 2018;Yigrem and Yohannes, 2019). Therefore, maize breeding programs in SSA typically incorporate GLS resistance in product pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the fndings of this investigation, Negash et al [25] observed that the combination of variety and split application time had a substantial impact on maize ear length. Similarly, the authors in [23] discovered that there was a considerable diference in ear length between the primary efects of diferent maize cultivars. According to Yusuf et al [26], diferent maize cultivars have dramatically varying cob lengths.…”
Section: Ear Length Te Results Of the Analysis Of Variancementioning
confidence: 89%
“…While the lowest 290 g was recorded from the interaction of the BH-546 variety with 1/2 dose N at planting and 1/2 dose of N at knee height (Table 8). Likewise, Ahmad et al [32] indicated that thousand grain weights were signifcantly afected by cultivars, their interaction between cultivars, and nitrogen time application [23]. It was established that the thousand-kernel weight showed signifcant diference at P < 0.05 among the main efect of maize varieties and their interaction between varsities and nitrogen time application.…”
Section: Number Of Kernel Per Earmentioning
confidence: 97%
See 1 more Smart Citation
“…, who found that higher disease pressure reduced grain yield, which was mostly due to increased blighting and premature death of photosynthetic tissues prior to grain filling. Similarly, Mengist and Moges (2019) found that local maize (check) had the largest yield loss (47.25 %) in maize varieties grown in the field, followed by AMR-852 maize variety with 47.25 % grain yield losses.…”
Section: Association Of Disease Parameters With Yield and Relative Yi...mentioning
confidence: 81%